Effectiveness of Culinary Industry MSME Brand Protection in Batam City - Ade Borami Ju; Hari Sutra Disemadi (Universitas Muhammadiyah Purworejo, 2023)
Intellectual Property (IP) is a right that originates from the creations of human thoughts, which are expressed in various forms and have economic or commercial value. One form of violation currently quite common in IP is counterfeiting or imitating marks. It is caused by developments in technology and transportation facilities which have caused activity in the trade sector, both goods, and services, to experience very rapid development. This study aimed to determine the effectiveness of brand protection for the MSME culinary industry in the city of Batam. This study uses non-doctrinal or empirical legal research methods with data collection techniques using primary and secondary data obtained through interviews and the results of literature studies. This study concludes that the legal protection of trademarks for MSME culinary industry business actors in Batam City is still ineffective. It cannot be applied to society as a whole, where based on culture, there are still quite a several business actors in the culinary industry in Batam City who still need to register their intellectual property. Many people still need to learn about Law Number 20 of 2016 concerning Marks as a law that all Indonesian people must obey as legal subjects.